2015
DOI: 10.1002/cbdv.201400119
|View full text |Cite
|
Sign up to set email alerts
|

Drimane Sesquiterpenoids from the Aspergillus oryzae QXPC‐4

Abstract: Three new drimane sesquiterpenoids, astellolides C-E (1-3, resp.), four new drimane sesquiterpenoid p-hydroxybenzoates, astellolides F-I (4-7, resp.), together with two known compounds astellolides A and B (8 and 9, resp.), have been isolated from the liquid culture of Aspergillus oryzae (strain No. QXPC-4). Their structures were established by comprehensive analysis of spectroscopic data. The relative and absolute configurations were determined on the basis of NOESY and CD data, together with single-crystal X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thus, A. oryzae produces kojic acid, the diterpene indoles aflavinines, the aflatrem precursor 13-desoxypaxilline, the sesquiterpenes parasiticolides and various alkaloids, e.g., ditryptoleucine and oryzamides [ 9 ]. Other compounds produced by A. oryzae have been reported recently [ 10 , 11 , 12 ]. However, identifications of the respective producing strains were solely based on morphological characteristics and ribosomal genes, which are insufficient to clearly differentiate them from A. flavus [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, A. oryzae produces kojic acid, the diterpene indoles aflavinines, the aflatrem precursor 13-desoxypaxilline, the sesquiterpenes parasiticolides and various alkaloids, e.g., ditryptoleucine and oryzamides [ 9 ]. Other compounds produced by A. oryzae have been reported recently [ 10 , 11 , 12 ]. However, identifications of the respective producing strains were solely based on morphological characteristics and ribosomal genes, which are insufficient to clearly differentiate them from A. flavus [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C NMR spectrum (Table 1) showed the presence of 15 carbon resonances which were classified using DEPT experiments into three methyls ( δ C at 33.4, 23.0, and 15.8), three methylenes (including one oxygenated methylene at δ C 80.9), six methines (including a double bond group at δ C 130.4 and 129.4; an oxymethine δ C 64.8; and a hemiacetal methine at δ C 101.7), and three quaternary carbons (including an oxygen-bearing carbon at δ C 79.0). These data suggested that 1 was a drimane sesquiterpenoid [16, 17]. Comparing the NMR spectra (Table 1) of 1 with those of 2 α -hydroxyisodrimeninol ( 4 ) [17, 18], a drimane sesquiterpenoid also isolated from this fungus, revealed that the two compounds were similar.…”
Section: Resultsmentioning
confidence: 95%
“…2). The relative configuration of 1 was deduced from the results of ROESY experiment and comparison with the data in literature [16, 17]. The ROESY correlations of Me-15 ( δ H 0.88) with H-2 ( δ H 3.91), H-11 ( δ H 5.37) and H a -12 ( δ H 3.70) revealed that these protons were β -oriented, and the ROESY correlation between H-5 ( δ H 1.93) and H-9 ( δ H 2.07) suggested their α -oriented configuration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 5-7 are drimane-type sesquiterpenoids with a furanone group without cytotoxic activity isolated from Aspergillus sp. [16]. Compared with astellolides B (6) and G (7), astellolide A (5) exhibited obvious phytotoxic activity, which may be related to the benzene ring without the phenol hydroxyl group.…”
Section: Discussionmentioning
confidence: 95%
“…Among these fractions, nine compounds were purified by repeated CC. Their structures were identified to be aspertamarinoic acid (1), (−)dihydrocanadensolide (2) [10], kojic acid (3) [11], citreoisocoumarin (4) [12,13], astellolide A (5) [14], astellolide B (6) [15], astellolide G (7) [16], cyclo-N-methylphenylalanyltryptophenyl (8) [17] and (−)-ditryptophenaline (9) [18] (Figure 2) on the basis of their HRESIMS, 1D and 2D NMR spectra (see Figures S1-S24) and compared with those reported in the previous literature. -3 ).…”
Section: Isolation Purification and Structure Elucidationmentioning
confidence: 99%